Investigating the use of electronic referrals to facilitate the patient referral process in Southern African public hospitals - Kapepo, Meke (Department of Information Systems, 2025)
Digital health interventions, particularly electronic referrals (e-referrals) and health information systems, have revolutionised clinical workflows in public hospitals by automating processes. However, the utilisation of e-referrals has yielded mixed outcomes, with varying levels of success in organisational processes. While most healthcare providers (HCPs) in high-income countries have effectively leveraged the benefits of e-referrals, those in low- and middle-income countries have been slower in their adoption and implementation. Consequently, there is a dearth of comprehensive studies documenting the successes and advantages of e-referrals in these contexts. Most studies highlight constraints and challenges related to the significant infrastructural challenges in low- and middle-income countries, ranging from limited internet access, insufficient user involvement, and design limitations within existing health information systems. Consequently, studies conducted in these settings primarily highlight rather than present the potential benefits of e-referrals. In the face of these limitations, HCPs resort to workarounds and improvisations in the form of Shadow Information Technologies (SIT) by using platforms such as WhatsApp to complete their work. Such workarounds, while practical, may not offer the same level of information security as they are neither mandated nor supported by the Information Technology (IT) department. The purpose of this study is to investigate the use of electronic referrals to facilitate the patient referral process in Southern African public hospitals. Employing a multiple case study strategy, the research examined use of e-referrals in two tertiary public hospitals in South Africa's Western Cape Province and Namibia's Khomas region through a comparative study. Additionally, the study explored workaround practices related to mandated health information systems in order to understand their occurrence and effect on referral outcomes. Semi-structured interviews were conducted with 31 HCPs in these settings, and a thematic approach was employed to analyse the data. The theoretical explanation of empirical findings was provided through the lens of the design-reality framework, the Process framework for Healthcare Information System Workarounds and Impacts, and the Systems Engineering Patient Safety model (SEIPS 3.0). The study findings show substantial evidence indicating design reality gaps between the HCP's requirements to complete work and the design of the referral applications in public hospitals where the research was conducted. As a result of these gaps, HCPs enacted workarounds in various forms, including the utilisation of Shadow IT, augmenting existing systems with alternative computer-based, telephonic, and paper-based referrals, and adapting the existing e-referral applications to accommodate work-related misfits. These practices suggested design-reality gaps. For instance, the ereferrals were inadequately designed and were not accommodating some of the real needs of HCPs. Furthermore, the design-reality gaps were attributed to inadequate functionalities of health information systems, poor management systems and structures, lack of end-user involvement and IT support, and the absence of relevant IT policies and policy awareness among HCPs. These gaps resulted in ineffective use of ehealth applications and enactment of workarounds to these e-health applications in both case studies. Additionally, the study found that electronic applications were introduced in these hospitals without a comprehensive understanding of the context and needs of HCPs. Existing e-health applications, such as the District Health Information Systems (DHIS 2) and the Vula application, did not fully support the referral process in public hospitals. In the one case study, Vula's implementation lacked adequate involvement from HCPs, failing to address their unique needs and contextual requirements. In the other case study, although DHIS2 was implemented as the national Health Information system in Namibia, it was not utilised for referral purposes but rather for administrative tasks. These challenges led to frustration and decreased satisfaction with the mentioned e-health applications, prompting HCPs to resort to workarounds to complete their work. These workaround practices stemmed from the autonomy exercised by HCPs to deliberately circumvent the mandated systems in order to achieve their tasks effectively and efficiently. The conceptual framework developed from the data explained these workaround practices emerging from design-reality gaps. The use of Shadow IT and workaround practices introduced unprecedented security risks to clinical information shared in shadow systems, compromising patient privacy and confidentiality. The study findings demonstrated that workarounds significantly amplified patient safety concerns and led to negative outcomes in the referral process and overall health organisations. In general, Shadow IT should not be viewed negatively, but should be viewed as opportunities for revealing the real needs and challenges encountered by HCPs. One could argue that the utilisation of Shadow IT not only exposes design-reality gaps in existing systems but also pinpoints the realities and demands of healthcare professionals within their specific environments. Consequently, Shadow IT provides innovative solutions to address limitations in the existing health information systems, particularly in enhancing healthcare delivery for referral processes. In conclusion, this research highlights the challenges and complexities in implementing electronic referrals in Southern African public hospitals. Understanding the underlying design-reality gaps and workaround practices can help health organisations develop more contextually relevant e-referral solutions to enhance patient safety and overall healthcare outcomes.